All-Climate Aluminum-Ion Batteries Based on Binder-Free MOF-Derived FeS2@C/CNT Cathode - Hu, Yuxiang; Huang, Hongjiao; Yu, Deshuang; Wang, Xinyi; Li, Linlin; Hu, Han; Zhu, Xiaobo; Peng, Shengjie; Wang, Lianzhou (Nano-Micro Letters, 2021)
Aluminum-ion batteries (AIBs) are promising next-generation batteries systems because of their features of low cost and abundant aluminum resource. However, the inferior rate capacity and poor all-climate performance, especially the decayed capacity under low temperature, are still critical challenges toward high-specific-capacity AIBs. Herein, we report a binder-free and freestanding metal–organic framework-derived FeS2@C/carbon nanotube (FeS2@C/CNT) as a novel all-climate cathode in AIBs working under a wide temperature window between −25 and 50 °C with exceptional flexibility. The resultant cathode not only drastically suppresses the side reaction and volumetric expansion with high capacity and long-term stability but also greatly enhances the kinetic process in AIBs with remarkable rate capacity (above 151 mAh g−1 at 2 A g−1) at room temperature. More importantly, to break the bottleneck of the inherently low capacity in graphitic material-based all-climate AIBs, the new hierarchical conductive composite FeS2@C/CNT highly promotes the all-climate performance and delivers as high as 117 mAh g−1 capacity even under −25 °C. The well-designed metal sulfide electrode with remarkable performance paves a new way toward all-climate and flexible AIBs. Highlights: 1 A binder-free and freestanding all-climate cathode FeS2@C/CNT in aluminum-ion batteries working from −25 to 50 °C with exceptional flexibility, enhanced capacity retention (above 117 mAh g−1) and rate capacity even at a low temperature of −25 °C. 2 High rate capacity (above 151 mAh g−1 at 2 A g−1) and robust long-term stability (above 80 mAh g−1 after 2,000 cycles at 1 A g−1) at room temperature. 3 DFT simulation verifies that the well-designed structure restricts FeS2 pulverization and facilitates the kinetic process of active ion.